The production of cox-free hydrogen and carbon nanofibers from direct catalytic decomposition of methane - Chai, Siang-Piao; Sharif Zein, Sharif Hussein; Mohamed, Abdul Rahman (2006)
Direct decomposition of methane was carried out using a fixed-bed reactor at 700oC for the production of COx-free hydrogen and carbon nanofibers. The catalytic performance of NiOM/ SiO2 catalysts (where M = AgO, CoO, CuO, FeO, MnOx, and MoO) in methane decomposition was investigated. The experimental results indicate that among the tested catalysts, NiO/SiO2 promoted with CuO gave the highest hydrogen yield. In addition, the examination of the most suitable catalyst support, including Al2O3, CeO2, La2O3, SiO2, and TiO2, shows that the decomposition of methane over NiO-CuO favors SiO2 support. Furthermore, the optimum ratio of NiO to CuO on SiO2 support for methane decomposition has been determined. The experimental results show that the optimum weight ratio of NiO to CuO fell at 8:2 (w/w) as the highest methane conversion was obtained over this catalyst.